Action arts: body and urban space resignification (2011)
The article analyzes action arts such as performance, happening and body art, emphasizing on their achievements both on artists and spectators and participants, when carried out in urban spaces amid recreational purposes. The author extends, among others, on the cultural, social, psychic, urban, andpolitical importance and reach of playfulness as an essential component of action arts: non-object-related works that provide the human body with different meanings and serve like individual and collective self recognition devices. It analyzes the city as scenario, as a non-discrimination space where artistic actions emerge as a subversive game that questions institutionalism and scrutinizes the whole apparatus accountable for theclassic and —even— modern art mystification that segregated certain audiences and artists. It points out that we are living in a time of diversity, difference and multiculturalism, hence, recognizing ourselves in artworks is getting to know something else about ourselves and conquering one truth about the world and the place we inhabit: the city.